Evolution of rabies in Greece from 1966 to 1980 - ΜΑΣΤΡΟΓΙΑΝΝΗ Μ.; ΜΑΓΓΑΝΑ Ο. (Journal of the Hellenic Veterinary Medical Society, 2019)
The authors observed during the last fifteen years 1966-1980 a decrease of rabies cases in Greece, after the increase noticed in the post World — war II period and they propose measures for the control of the rabies.